Dynastic Politics and Party Persistence: Mechanisms of Elite Power Reproduction in Indonesian Democracy 2024 Elections - Moch. Fauzie Said; Novy Setia Yunas (UIN Sunan Gunung Djati, 2025)
This study critically examines how dynastic politics and party persistence reproduce elite power in Indonesia’s 2024 elections. It highlights a central paradox: elections remain procedurally competitive, yet democracy’s substance is increasingly weakened by oligarchic consolidation. Using a qualitative approach, the research combines a systematic review of literature with critical discourse analysis. The findings show that dynastic politics has become entrenched in both executive and legislative institutions. Nearly 30 percent of parliamentary members are linked to political families, while the rise of Gibran Rakabuming Raka, son of President Joko Widodo, as vice president reflects the normalization of political dynasties in democratic settings. Party persistence is reinforced through cartelization, bureaucratic co-optation, and strategic alliances that cut across ideology. Together, these dynamics create a pattern of “elite circulation without renewal,” where leadership changes but power remains concentrated within oligarchic networks. The implications are profound: Indonesia risks becoming a pseudo-democracy in which electoral procedures continue but meaningful competition, representation, and accountability are hollowed out. This contributes to democratic backsliding and narrows the space for citizen participation. By integrating classical elite theory with contemporary Indonesian evidence, this study highlights how dynastic politics and party persistence function as dual mechanisms of elite power reproduction.